From pathogenesis to treatment: the emerging role of ferroptosis in Parkinson’s disease - Tu, Ruoxin; Han, Zhongyu; Zhang, Hongbo; Jia, Xiaoye; Sun, Tong; Liu, Hanlin; Li, Jingxian; Tang, Mingke; Wang, Shun (Frontiers in Immunology, 2025)
Parkinson’s disease (PD), the second most common neurodegenerative disorder worldwide, features gradual loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) along with pathological α-synuclein (α-syn) aggregation. Recently, emerging evidence has identified ferroptosis, an iron-dependent regulated cell death, as a pivotal factor in driving PD pathogenesis, with close associations to key mechanisms including α-syn protein aggregation, excessive oxidative stress, mitochondrial dysfunction, disturbances in iron metabolism, and activation of neuroinflammatory responses. This distinct mode of regulated cell death provides novel perspectives for understanding the underlying pathogenesis of PD. This review highlights the mechanisms of ferroptosis, its contribution to PD pathogenesis, evidence from animal models, and clinical advances in ferroptosis-targeted therapies. Moreover, we put forward the potential of ferroptosis in the early diagnosis and treatment of PD. A profound understanding of the ferroptosis-PD crosstalk provides a new perspective on neuronal vulnerability and holds promise for advancing novel treatments for this disabling disorder.